Manejemen Program Unggulan Pondok Pesantren Al-Madani Cikalong Majalengka - Alifatuz Zahro (Balitbangda Provinsi Jambi, 2022)
Abstract The quality of an educational institution, one of which is a boarding school, is influenced by the quality of the main program at the pesantren. A main program will determine the output of the pesantren. This study aims to explore and identify the superior main management of the Al-Madani Islamic Boarding School Cikalong, Majalengka. Management studies emphasize the planning, implementation, and evaluation of flagship programs. This research uses a qualitative research approach with the type of case study research. Collecting data in this study using in-depth interviews and literature study. The results of this study include: (1) the flagship program of the Al-Madani Islamic Boarding School, namely the Tahfizul Qur'an program, (2) the implementation of the Tahfizul Qur'an program has been carried out intensely since the 3rd grade of junior high school, (3) the evaluation of this program is carried out with the parents of students . Keywords: Management, Featured Program, Tahfizul Qur'an, Islamic Boarding School Abstrak Kualitas sebuah lembaga pendidikan, salah satunya pondok pesantren dipengaruhi oleh kualitas program unggulan di pesantren tersebut. Sebuah program unggulan akan menentukan output dari pesantren. Penelitian ini bertujuan untuk mengeksplor dan mengidentifikasi manajemen program unggulan dari Pondok Pesantren Al-Madani Cikalong, Majalengka. Kajian manajemen ditekankan pada perencanaan, pelaksanaan, dan evaluasi program unggulan. Penelitian ini menggunakan pendekatan penelitian kualitatif dengan jenis penelitian studi kasus. Pengambilan data pada penelitian ini menggunakan wawancara mendalam dan studi pustaka. Hasil dari penelitian ini diantaranya: (1) program unggulan Pondok Pesantren Al-Madani yaitu program Tahfizul Qur'an, (2) pelaksanaan program Tahfizul Qur'an dilaksanakan secara intens sejak kelas 3 SMP, (3) Evaluasi program ini dilaksanakan bersama orangtua santri. Kata Kunci: Manajemen, Program Unggulan, Tahfizul Qur'an, Pesantren Abstract The quality of an educational institution, one of which is a boarding school, is influenced by the quality of the main program at the pesantren. A main program will determine the output of the pesantren. This study aims to explore and identify the superior main management of the Al-Madani Islamic Boarding School Cikalong, Majalengka. Management studies emphasize the planning, implementation, and evaluation of flagship programs. This research uses a qualitative research approach with the type of case study research. Collecting data in this study using in-depth interviews and literature study. The results of this study include: (1) the flagship program of the Al-Madani Islamic Boarding School, namely the Tahfizul Qur'an program, (2) the implementation of the Tahfizul Qur'an program has been carried out intensely since the 3rd grade of junior high school, (3) the evaluation of this program is carried out with the parents of students . Keywords: Management, Featured Program, Tahfizul Qur'an, Islamic Boarding School